The lies of locke lamora eaudiobook - Lynch, Scott (Gentleman Bastard, 2019)
The first book of the epic fantasy caper Gentleman Bastard Sequence about a roguish group of conmen, which George R. R. Martin says “captured me right on the first page and never let me go.”   “If you haven’t read [ The Lies of Locke Lamora ], you should. If you have read it, you should probably read it again.”—Patrick Rothfuss An orphan’s life is harsh—and often short—in the mysterious island city of Camorr. But young Locke Lamora dodges relentless danger, becoming a thief under the tutelage of a gifted con artist. As leader of the band of light-fingered brothers known as the Gentlemen Bastards, Locke is soon infamous, fooling even the underworld’s most feared ruler. But in the shadows lurks someone still more ambitious and deadly. Faced with a bloody coup that threatens to destroy everyone and everything that holds meaning in his mercenary life, Locke vows to beat the enemy at his own brutal game—or die trying.   Don’t miss any of Scott Lynch’s epic fantasy Gentleman Bastard Sequence: THE LIES OF LOCKE LAMORA • RED SEAS UNDER RED SKIES • THE REPUBLIC OF THIEVES